Efficacy of subanaesthetic esketamine on the prevention of postoperative delirium in older adult patients after cardiovascular surgery: protocol for a single-centre, randomised, double-blind, placebo-controlled trial (SEPDOC trial) in China - Wei Zhang; Liang Zhao; Ju-Min Yan; Qing-Ren Liu; Jian-Jun Yang; Hong-Qi Lin; Zhao-Yu Wen; Hao-Ran Zhang; Yi-Xin Mei; Rui-Di Wang (BMJ Open)
Introduction Postoperative delirium (POD) is a common and serious complication in older adult patients undergoing cardiovascular surgery. Esketamine is known for its anti-inflammatory and neuroprotective properties. While it has shown preventive effects on POD in those not undergoing cardiovascular surgery, its efficacy in older adult patients undergoing cardiovascular surgery remains uncertain. Therefore, we herein aimed to evaluate the preventive effect of intraoperative subanaesthetic esketamine on POD in this specific population.Methods and analysis This single-centre, randomised, double-blind, placebo-controlled trial will enrol 778 patients aged 60–80 years undergoing open-heart cardiovascular surgery in China, from September 2023 to December 2025. The participants will be randomly assigned in a 1:1 ratio to the following groups: the esketamine group and the control group. In the esketamine group, esketamine (2 mg/mL) will be administered intravenously at a dosage of 0.3 mg/kg over 10 min following tracheal intubation, followed by a continuous infusion at 0.15 mg/kg/h until the end of the surgery. Patients in the control group will receive a placebo following the same dosage and regimen. The incidence of POD will be the primary outcome and will be assessed twice daily from the first to the seventh postoperative day. The postoperative sleep quality, duration of postoperative mechanical ventilation, and length of hospital and intensive care unit stay will be the secondary outcomes.Ethics and dissemination Ethical approval was obtained from the Institutional Review Board of Fuwai Central China Cardiovascular Hospital (No. 2023068). Public disclosure is guaranteed post-trial, and the results will be published in a peer-reviewed scientific journal.Trial registration number ChiCTR2300074395.